Incorporating channel network information in hydrologic response modelling: Development of a model and inter-model comparison. (February 2017) - Biswal, Basudev; Singh, Riddhi
Highlights: A new channel network based model is proposed to simulate full hydrographs including flood and recession limbs. The proposed model is tested against a commonly used routing scheme in a multi-objective framework. The proposed model generally betters at capturing low flows and dynamic storage-discharge relationship. Abstract: Incorporation of channel network information in streamflow modelling is a well-accepted scientific practice now. In particular, channel network morphology based instantaneous unit hydrographs (IUHs) are widely used for modelling of flood response. However, very few attempts have been made so far to use channel networks for modelling total flow, not just flood flow. In this study, total flow is partitioned into pure surface flow (PSF) and mixed surface-subsurface flow (MSSF), which are then modelled separately by constructing channel network morphology based IUHs. For modelling total flow, the combined IUH is then obtained by introducing a splitting parameter that represents the relative proportions of PSF and MSSF. We compare the performance of the proposed geomorphology based routing structure and a variant with a commonly used routing structure – two linear reservoirs in parallel. The three routing structures are then integrated with a well-known water balance model to perform continuous streamflow modeling. We perform inter-model comparison quantitatively by considering eight performance metrics within a multi-objective framework as well as qualitatively by observing the simulated storage-discharge relationships. By performing the inter-model comparison for 71 catchments across the US, we find that the geomorphology based models perform better than the linear model for low flow related metrics. They are also better at capturing non-linear and dynamic relationship between catchment water storage and discharge. The geomorphology based models perform particularly well in northeastern and midwestern US, while no such region of dominance emerges for the linear routing based model. Results also indicate the possibility of using the proposed models to capture the dominant flow generation processes in a basin.